From Precursor Powders to CsPbX3 Perovskite Nanowires: One‐Pot Synthesis, Growth Mechanism, and Oriented Self‐Assembly. Issue 44 (26th September 2017) - Tong, Yu; Bohn, Bernhard J.; Bladt, Eva; Wang, Kun; Müller‐Buschbaum, Peter; Bals, Sara; Urban, Alexander S.; Polavarapu, Lakshminarayana; Feldmann, Jochen
Abstract: The colloidal synthesis and assembly of semiconductor nanowires continues to attract a great deal of interest. Herein, we describe the single‐step ligand‐mediated synthesis of single‐crystalline CsPbBr3 perovskite nanowires (NWs) directly from the precursor powders. Studies of the reaction process and the morphological evolution revealed that the initially formed CsPbBr3 nanocubes are transformed into NWs through an oriented‐attachment mechanism. The optical properties of the NWs can be tuned across the entire visible range by varying the halide (Cl, Br, and I) composition through subsequent halide ion exchange. Single‐particle studies showed that these NWs exhibit strongly polarized emission with a polarization anisotropy of 0.36. More importantly, the NWs can self‐assemble in a quasi‐oriented fashion at an air/liquid interface. This process should also be easily applicable to perovskite nanocrystals of different morphologies for their integration into nanoscale optoelectronic devices. Abstract : Cubes, wires, and assemblies : Single‐crystalline perovskite nanowires were prepared directly from precursor powders in a single‐step ligand‐assisted process by ultrasonication. The nanowires likely resulted from the oriented attachment of nanocubes. Quasi‐oriented self‐assemblies of the perovskite nanowires were fabricated at air/liquid interfaces.